Application of polymeric nanofluid in enhancing oil recovery at reservoir condition - Augustine, Agi; Radzuan, Junin; Mohammed Omar, Abdullah; Mohd Zaidi, Jaafar; Agus, Arsad; Wan Rosli, Wan Sulaiman; M.N.A., MohdNorddin; Muslim, Abdurrahman; Azza, Abbas; Afeez, Gbadamosi; Nur Bashirah, Azli (Elsevier, 2020)
In this study, ascorbic acid was used to synthesize Cissus populnea nanoparticles (CPNP). The synthesized CPNP was isolated and the influence of the process variables on the physical properties were studied. The rheology of the formulated Cissus populnea nanofluid (CPNF) was measured and compared with Cissus populnea (CP) solution and commercial polymer xanthan. Moreover, the interfacial properties of CPNF were studied at various concentrations and temperatures, and the influence of salinity and their interaction with ultrasound was investigated. Sessile drop contact angle method was used to determine the wettability alteration efficiency of CPNF on an initially oil-wet sandstone core surface. Finally, CPNF and CP solutions were evaluated for EOR purposes at typical reservoir condition. The displacement process was scaled to reduce the number of parameters investigated using dimensionless parameters. The synthesis methods were efficient in generating sphere-shaped and elongated nanoparticles (50 nm mean diameter). Experimental results show that an increase in temperature of CP and CPNP yielded increased viscosity of the solutions in stark contrast to xanthan whose solution viscosity declines as the temperature increases. Besides, the CPNF was effective in lowering IFT at oil-water (O/W) interface and altered the wettability of the sandstone cores to water-wetting condition. The novel CPNF increased the oil recovery by 26% and was effective at high-temperature high-pressure (HTHP) reservoir condition. The result shows a transition from capillary dominated flow to gravity dominated flow as decrease in IFT decreased residual oil saturation and increased capillary and Bond number. The energy consumption and cost estimation of the proposed novel polymeric nanofluid shows it is cost-effective than conventional EOR chemicals.